Cando o pasado é futuro: historia e construción nacional na Galiza do século XIX - Viveiro Mogo, Prudencio (Madrygal. Revista de Estudios Gallegos, 2009)
Throughout the time one of the functionalities that more frequently has given to the History has been it of serving as support of political ideas. The historiography discourse has served, then, as base of a certain political project. In the past the reasons were looked to base a certain present, when not a glorious future. In this work we try to investigate which has been the influence of the Galician historiography in the process of national building of Galicia in the 19th century. In general, we can say that we pass from an apologetic history, which it was trying to place Galicia as one of the first Spanish people, to a differential history, that had in the Celtism the center of his discourse.